Effect of Temperature and Cell Viability on Uranium Biomineralization by the Uranium Mine Isolate Penicillium simplicissimum - Schaefer, Sebastian; Steudtner, Robin; Hübner, René; Krawczyk-Bärsch, Evelyn; Merroun, Mohamed L. (Frontiers in Microbiology, 2021)
The remediation of heavy-metal-contaminated sites represents a serious environmental problem worldwide. Currently, cost- and time-intensive chemical treatments are usually performed. Bioremediation by heavy-metal-tolerant microorganisms is considered a more eco-friendly and comparatively cheap alternative. The fungus Penicillium simplicissimum KS1, isolated from the flooding water of a former uranium (U) mine in Germany, shows promising U bioremediation potential mainly through biomineralization. The adaption of P. simplicissimum KS1 to heavy-metal-contaminated sites is indicated by an increased U removal capacity of up to 550 mg U per g dry biomass, compared to the non-heavy-metal-exposed P. simplicissimum reference strain DSM 62867 (200 mg U per g dry biomass). In addition, the effect of temperature and cell viability of P. simplicissimum KS1 on U biomineralization was investigated. While viable cells at 30 °C removed U mainly extracellularly via metabolism-dependent biomineralization, a decrease in temperature to 4 °C or use of dead-autoclaved cells at 30 °C revealed increased occurrence of passive biosorption and bioaccumulation, as confirmed by scanning transmission electron microscopy. The precipitated U species were assigned to uranyl phosphates with a structure similar to that of autunite, via cryo-time-resolved laser fluorescence spectroscopy. The major involvement of phosphates in U precipitation by P. simplicissimum KS1 was additionally supported by the observation of increased phosphatase activity for viable cells at 30 °C. Furthermore, viable cells actively secreted small molecules, most likely phosphorylated amino acids, which interacted with U in the supernatant and were not detected in experiments with dead autoclaved cells. Our study provides new insights into the influence of temperature and cell viability on U phosphate biomineralization by fungi, and furthermore highlights the potential use of P. simplicissimum KS1 particularly for U bioremediation purposes.